A combination of fuzzy positioned dental X-ray analysis model to presume the peculiar images. Issue 1 (2nd January 2020) - Buhari, M. P. A.; Mohideen, S. K.
ABSTRACT: Dental X-ray segmentation is one of the most important and necessary steps to analyze the dental images for better medical diagnosis. The aim of this work is to develop an effective method for the prediction of normal and abnormal images using classification process. The hybrid fuzzy-based classification model (HFCM) includes the hybridization of Bayesian hidden morkov model and fuzzy classifier. Parameters such as accuracy, specificity, sensitivity, precision, and computational time are calculated to assess the robustness of the proposed approach.